The Experience of English Education Undergraduate Students in Writing a Thesis in the Age of AI - Primatur Riyana; Durratul Hikmah (PT PUSTAKA CENDEKIA GROUP, 2026)
The rapid development of Generative Artificial Intelligence (Gen-AI) has transformed the way undergraduate students complete academic writing, particularly in English as a Foreign Language (EFL) contexts. While previous studies have mainly examined the effectiveness and challenges of AI, limited attention has been given to students’ lived experiences throughout the thesis-writing process. This study aimed to explore the experiences of English Education undergraduate alumni in writing their undergraduate theses in the age of Artificial Intelligence. A qualitative study with a phenomenological design was employed. Six alumni of the English Education Department at Universitas Nurul Jadid, who graduated in 2024 and 2025, were purposively selected as participants. Data were collected through semi-structured interviews using Google Forms and follow-up interviews via Telegram and analyzed using Interpretative Phenomenological Analysis (IPA). The findings revealed three major themes: (1) students integrated AI into the pre-writing, writing, and post-writing stages primarily for brainstorming, language improvement, and proofreading; (2) they encountered challenges related to linguistic limitations, overreliance on AI, and concerns about academic integrity; and (3) they developed various strategies, including critical evaluation of AI-generated content, consultation with supervisors, and responsible AI use to maintain originality. The study concludes that AI functions as a valuable writing assistant rather than a replacement for students' academic thinking when it is used critically and ethically.